2009
DOI: 10.1002/lt.21797
|View full text |Cite
|
Sign up to set email alerts
|

Role of splanchnic hemodynamics in liver regeneration after living donor liver transplantation

Abstract: The aim of this study was to investigate the changes in splanchnic hemodynamics after LDLT and their relationship with graft regeneration. Eighteen patients with LDLT December 2006 and June 2008 were enrolled, and color Doppler ultrasonography was performed preoperatively and on postoperative days (PODs) 1, 3, 5, 7, 30, and 90 after transplantation. The changes in the portal blood flow mean velocity (PBV) and portal blood flow volume (PBF) were monitored, and their effects on hepatic function were observed sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Regarding correlation between blood flow and organ volume, portal blood flow was associated with degree of liver regeneration after hepatectomy 26 as well as after liver transplantation 27 . Our finding is more likely to be collateral evidence that blood flow can be a determinant of lung volume in normal lung development.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding correlation between blood flow and organ volume, portal blood flow was associated with degree of liver regeneration after hepatectomy 26 as well as after liver transplantation 27 . Our finding is more likely to be collateral evidence that blood flow can be a determinant of lung volume in normal lung development.…”
Section: Discussionmentioning
confidence: 98%
“…[10] On the contrary, other studies found significant correlations between PVVs and various other indices representing hepatic regeneration obtained at different postoperative time points. [2,9] However, these studies did not analyze data with PVV/GW. At this point, it is difficult to explain discrepancies in results between the studies because of differences in study designs.…”
Section: Discussionmentioning
confidence: 99%
“…[10] However, this study also included 3 patients with fulminant hepatic failure and assessed the hepatic regeneration rate earlier than 2 weeks after LDLT, when the effects of early graft edema on the liver graft are still prevalent. Lastly, Jiang et al's study, [9] which showed the correlations of PVV and PVF on POD 1 and 3 with percent change in GW between preoperative period and POD 30, included only 18 patients. All the above studies standardized only the surgical technique without considering standardization of anesthetic management.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al [29] demonstrated that modulation of portal flow to prevent hyperperfusion through splenic artery ligation or splenectomy can promote graft regeneration. Jiang et al [30] also demonstrated that portal hyperperfusion has to be kept under 300 ml/min per 100 g of hepatic tissue to maintain regeneration of the graft.…”
Section: Hemodynamics and Allograft Functionsmentioning
confidence: 96%